Investigating the Learning Phase of an Autonomous Authentication in Mobile Ad-hoc Networks - Zhang, Hang; Memarmoshrefi, Parisa; Ashrafi, Fatemeh; Hogrefe, Dieter (EAI Endorsed Transactions on Security and Safety, 2016)
In this work we focus on investigating the learning phase of an autonomous authentication mechanism. Through a series of simulation, an experimental best cutoff point and the aggression threshold values for different network size were calculated. In the test phase, those found values are proved by the average good accuracy.
Keywords: aggression/distrust; public key certificate chain; attacker; ad-hoc networks